Formation behaviors of networks with antagonistic interactions of agents - Wen-Lu Zou; Gun Li (International Journal of Distributed Sensor Networks)
In this study, a new formation behavior problem for second-order multi-agent systems with time delay is investigated in the presence of antagonistic interactions. We first proposed a formation behavior protocol with time delay for each agent in the antagonistic network. Then, by a frequency-domain analysis, a sufficient and necessary condition is derived to guarantee the consensus stability of the multi-agent system. It is shown that the agents in the same group form their own desired formation while keeping a desired relative position with other groups. Finally, numerical simulations are provided to illustrate the obtained results.